Concept of Waqf in Supporting Health Facilities and Its Compliance With Regulation in Indonesia - Muhammad Sena Nugraha Pamungkas; Irham Zaki (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This study aims to identify the concept and utilization of waqf in supporting and running health care facilities in Islamic civilization and evaluating its compliance with statutory regulations if the same concept is applied in Indonesia. By using the documentary research method this study examining and/or exploring various secondary sources related to the research topic. This research concludes that the use of waqf in supporting and maintaining the sustainability of health facilities has become a part of Islamic civilization. The concept of using waqf in operating and supporting health facilities is also not against the prevailing laws and regulations. In fact, the concept is in the same line with article 170 of Law No. 36 of 2009 concerning health and Presidential Decree No.59 of 2017 concerning sustainable development. With the harmony between the concept of waqf and the prevailing law and regulations it is expected that government could realizing provided a sustainable and inclusive waqf-based development.